Social policy and citizenship: the changing lanscape (New York, 2013)
"In both Europe and America, the landscape of social policies has undergone fundamental changes in recent decades, especially in endeavors to develop new welfare arrangements. How does this affect citizenship-at-large as defined by the Marshallian triad of personal, democratic, and social rights?